2019
DOI: 10.1504/ijsss.2019.098197
|View full text |Cite
|
Sign up to set email alerts
|

A study on impact of students perceived service quality on brand performance of self-financing engineering institutions

Abstract: Higher education engineering institutions in India faces a tough competition in getting the students, the students perception towards the institution depends upon the brand image of the institution. This scenario pushes the engineering education to think about branding and positioning in the competitive market and which can help to give the college the unique position in the market and help in gaining competitive advantage. This study aims at assessing the perceived service quality of the self financing engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It is, therefore, essential to analyse such quality-assurance systems that are being applied among the Philippine universities. Although there is a plethora of studies relating to TQM, most of the research projects have been preliminary, theoretical, and conceptual, whether concentrating on adapting the strategies of management of tertiary institutions, or by incorporating the expertise from other countries (Aljuhani, 2019, Alzafari & Kratzer, 2019, Cudney et al, 2020, Kumar et al, 2018, Murmura et al, 2016, Nurcahyo et al, 2019, Olcay & Bulu, 2017, Wen et al, 2018. Some of the TQM studies were found to be relating to business firms, such as foods and non-food manufacturing and production (Cho et al, 2017, Ding et al, 2019, Florkowski & Jiang, 2017, Kong et al, 2016, Liao et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, essential to analyse such quality-assurance systems that are being applied among the Philippine universities. Although there is a plethora of studies relating to TQM, most of the research projects have been preliminary, theoretical, and conceptual, whether concentrating on adapting the strategies of management of tertiary institutions, or by incorporating the expertise from other countries (Aljuhani, 2019, Alzafari & Kratzer, 2019, Cudney et al, 2020, Kumar et al, 2018, Murmura et al, 2016, Nurcahyo et al, 2019, Olcay & Bulu, 2017, Wen et al, 2018. Some of the TQM studies were found to be relating to business firms, such as foods and non-food manufacturing and production (Cho et al, 2017, Ding et al, 2019, Florkowski & Jiang, 2017, Kong et al, 2016, Liao et al, 2018.…”
Section: Introductionmentioning
confidence: 99%